2012
DOI: 10.1177/0733464812456632
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Forgiveness to Enhance the Health Status of Older Male Prisoners Confronting Spiritual, Social, or Emotional Vulnerability

Abstract: Participants in this study included 261 men, aged 45 and older, residing within state-managed correctional facilities in Oklahoma. Path analysis was used to examine an integrated mediation model. Spiritual ambivalence, loneliness, and depressive affect had direct negative associations with forgiveness, controlling for age, race, education, and type of crime. Forgiveness also maintained a direct positive association with perceived health status, whereas depressive affect maintained a direct negative association… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In response to the hardship of imprisonment, ageing prisoners adopt various coping mechanisms, such as religion and spirituality (Leigey, ). In contrast with younger prisoners, who tend to hide their religious belief from their peers, ageing prisoners often pride themselves over a rich spiritual life (Reed, ), which alleviates feelings of depression, anxiety and fear (Bishop et al , , Allen et al , ; Allen et al , ), thus promoting “inner peace” (see Table ). Attending religious ceremonies also represents an opportunity for social life and connectedness (Reed, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the hardship of imprisonment, ageing prisoners adopt various coping mechanisms, such as religion and spirituality (Leigey, ). In contrast with younger prisoners, who tend to hide their religious belief from their peers, ageing prisoners often pride themselves over a rich spiritual life (Reed, ), which alleviates feelings of depression, anxiety and fear (Bishop et al , , Allen et al , ; Allen et al , ), thus promoting “inner peace” (see Table ). Attending religious ceremonies also represents an opportunity for social life and connectedness (Reed, ).…”
Section: Resultsmentioning
confidence: 99%
“…With the passage of time, prisoners may come to accept responsibility for their offence and their sentence. This may bring a change in attitude towards the victim(s) of their crime and the judicial authority, as well as emerging personal forgiveness for their wrongdoing (Bishop et al , ). Ageing prisoners also resort to reminiscing, the recalling of happy memories and/or challenging past events successfully dealt with, to find the strength to face the present (Crawley, ; Leigey , ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has found that, for some special populations, state and trait loneliness is closely related to hypothalamic–pituitary–adrenal activity when controlling depression and negative emotion (Zilioli et al, 2017). Furthermore, a significant correlation was found between prisoners' forgiveness and their loneliness and depression (Bishop, Randall, & Merten, 2014). Forgiveness is kind of internal control index.…”
Section: Discussionmentioning
confidence: 99%
“…The variables chosen to be tested have been previously shown to be predictors of loneliness in other populations. Lonely individuals are more likely to be low on extraversion and high on neuroticism (Abdellaoui et al, 2018; Atak, 2009), have lower levels of emotional intelligence (EI) or emotional competence (EC) (Wols et al, 2015; Zou, 2014), have higher levels of anxiety and depression (Fung et al, 2017; Peerenboom et al, 2015), and a lower ability to forgive (Bishop et al, 2014; Day & Maltby, 2005). Situational predictors of loneliness include unemployment (Lauder et al, 2004; Yan et al, 2014), low education (Cohen-Mansfield & Parpura-Gill, 2007; Hector-Taylor & Adams, 1996), low income (Beutel et al, 2017; Cohen-Mansfield & Parpura-Gill, 2007), and marital status (Pinquart & Sorensen, 2001).…”
Section: Assumptions and Rationale For The Current Studymentioning
confidence: 99%